Practical embedded controllers design and troubleshooting with the Motorolla [i.e. Motorola] 68HC11 - Park, John. (Oxford ; Burlington, MA : Newnes, 2003)
This book will help the technician, engineer and user understand the microcontroller-based systems along with the most common problems and their solutions. This book covers design, specification, programming, installation, configuration and of course troubleshooting. An engineer's guide to the design, applications and troubleshooting of microcontroller-based systems The introductory chapters on embedded microcontroller architecture and programming are written at the right level with an applications focus for practicing engineers A highly topical book with a wide readership involved with product design and industrial processes including control systems.
Introduction; CPU Design and Functions; Programming; Memory Mapping; Inputs and Outputs; Noise Reduction; Data Communications; Grounding Solutions; Installation Techniques; Conclusion; Appendix A: 68HC11 : Instruction Set; Appendix B: HC11 -- EVM Users Information; Appendix C: ASM11 -- Users Information; Appendix D: Procomm Users Information; Appendix E: PAT -- Software Users Information; Appendix F: Sample Programs; Appendix G: Practicals.
Includes bibliographical references and index.
Keywords: Embedded computer systems -- Design and construction; Motorola 68HC11 (Microprocessor); Motorola 68HC11 (Microprocessor) -- Maintenance and repair; Electronic books